Optimization of Braking Phase Coordinates for Energy-Efficient Operation of Pneumatic Systems - Strizhak M.; Rogovyi А.; Iglin S. (Problems of the Regional Energetics, 2025)
The aim of this study is to optimize the operating mode of a pneumatic system by determining the braking start and end coordinates that minimize the piston speed without the use of damping devices. This approach avoids the discharge of compressed air into the atmosphere and brings the operating conditions closer to an energy-saving mode. The goal is achieved through the implementation of a control algorithm that switches the distributor based on the piston position, allowing for the formation of a defined braking trajectory. The study involved mathematical modeling of the transient processes in the pneumatic system, as well as numerical optimization of the braking coordinates using the Nelder–Mead method and exhaustive search. It was found that the optimal braking start and end coordinates should be located within the last 10–15% of the piston stroke to ensure a final velocity of about 0.03 m/s. The most significant result is the development of a generalized dependency between braking coordinates and cylinder stroke length, enabling the design of energy-efficient pneumatic drive modes without the need for additional experimental research. As a result of the optimization, effective piston braking is achieved without damping devices, reducing compressed air losses and increasing the overall energy efficiency of the pneumatic system.